Effect of 1-Methylcyclopropene (1-MCP) on Quality and Shelf-Life of Banana Fruits (University of Khartoum Journal of Agricultural Sciences, 2023)
The effect of 1-Methylcyclopropene (1-MCP) on quality andshelf–life of ‘Grand Nain’ banana fruits was evaluated.1-Methylcyclopropene at 62.5, 125 and 250 ppb delayed fruit ripening,maintained quality and extended shelf-life of banana fruits. The higher theconcentration of 1-MCP, the more was the effect. 1-Methylcyclopropenesignificantly delayed the onset of the climacteric peak. The untreatedfruits reached the climacteric peak after 8 days at 18± 1°C and 85% - 90%relative humidity. Treatment with 1-MCP at 62.5, 125 and 250 ppbsignificantly delayed the onset of the climacteric peak by 12, 16 and 20days, respectively, compared with the untreated fruits. The effect of 1-MCP was also reflected similarly in retarded peel colour development andtotal soluble solids (TSS) accumulation, reduced fruit flesh softening andweight loss, and retained ascorbic acid content during storage of bananafruits.
Keywords: Banana fruit; 1-MCP; quality; shelf-life